Wings for life in the Guamuhaya Butterflies: the importance of a project - Eneida Bravo Polanco; Asleny Sánchez Leandro (Medisur)
During 2020, 3,887 people in Cuba were diagnosed with breast cancer, which represents a rate of 39.6, and 1,714 died, for a rate of 30.4. After a mastectomy, many things change in a woman's life, so she needs a lot of support. The “Wings for Life” project was created to support and provide information. Today the importance of this is a reality. The purpose of this research is to expose the criteria of the mastectomized women who are part of the Mariposas del Guamuhaya group, created in Cumanayagua, Cienfuegos province, as part of the “Alas por la vida” project, as well as to leave a graphic record of the activities they carry out and the contributions that it has made to the lives of these women in the human order.